Energy storage performance of Nd3+-doped BiFeO3–BaTiO3-based lead-free ceramics. Issue 20 (15th October 2022) - Khesro, Amir; Khan, Fawad Ahmad; Muhammad, Raz; Ali, Asif; Khan, Majid; Wang, Dawei
Abstract: Lead-free ceramics 0.7(Bi1- x Nd x )[Fe0.95 (Li0.5 Nb0.5 )0.05 ]O3 -0.3BaTiO3 +0.1 wt% MnO2 ( x = 0–0.05) solid solutions were synthesized through a solid state sintering route. Phase analysis showed the formation of a single/mixed perovskite structure for all samples. A morphotropic phase boundary between rhombohedral R3c and cubic P m 3 ‾ m appeared in all the samples. The microstructure analysis revealed well-densified ceramics with clear grains and grain boundaries. The dielectric measurement showed broadened and frequency-dependent dielectric maxima, indicating relaxor behavior. With an increase in Nd 3+ concentration, the temperature of maximum relative permittivity ( T m ) shifted from 564 °C to 330 °C ( x = 0.05). The breakdown strength (BDS) was significantly enhanced from 200 kV/cm ( x = 0) to 290 kV/cm ( x = 0.03). A maximum recoverable energy (Wrec = 3.2 J/cm 3 ) and a high conversion efficiency (η = 73.7%) was achieved for sample x = 0.03, showing promise for use in pulse power systems.